Firearm-related injuries in Cape Town children and youth 1992-1996 - Wigton, Alyssa (Division of Forensic Medicine and Toxicology, 2014)
The aim of this study was to determine the epidemiological profile of firearm-related injuries among children and youth under 19 years of age in Cape Town during the period 1 January 1992 - 31 December 1996. The purpose of the study was to make recommendations for future research, policies, prevention programmes and surveillance.